"Red silence": Ben Jonson and the Breath of Sound. Issue 1 (May 2019) - Wright, Laura Jayne
Abstract : In the prologue to Every Man in His Humour, Ben Jonson dismissed sound effects in favour of the spoken word; yet, throughout his work, Jonson uses sound to shocking and even violent effect. By examining the acoustics of Jonson's poem, A Panegyre on the Happy Entrance of James… to His First High Session of Parliament (1604), this article demonstrates that Jonson developed a distinct theory of sound, drawn from and often disagreeing with the work of Aristotle and Horace. It considers Jonson's pencil annotations on a copy of Thomas More's Carmen Gratulatorium (1509), to which his own poem is greatly indebted, and shows that these annotations are often made beside lines concerned with noise. Jonson's acoustic theory – which is dependent on an early modern understanding of the voice and of breath – is then traced throughout three of his comedies ( Volpone, The Alchemist, and Epicoene ). The article finally considers the responses of early readers of Jonson's dramatic work and their engagement with his sonic stage directions in Epicoene . It concludes that Jonson equivocates about the importance of sound, dismissing such "noise" only to discuss it at length in the next breath.